Kontraktion & Konvergenz: Probleme der nachhaltigkeitsökonomischen Generalisierung eines klimapolitischen Zukunftsmodells - Károly Henrich (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2006)
Contraction & Convergence' (C&C) is a model for the future. It is based upon the view, supported by indicators such as the 'ecological footprint', that human levels of natural resource consumption already overstep the ecological capacity of the Earth System by about 20% and must urgently be limited, at least to the level of this global eco-capacity. This process of contraction will only be politically acceptable and enforceable worldwide if it is linked to the equity aspect, the major disparities in natural resource consumption being removed through a process of convergence accompanying that of contraction. However, until now expansion and divergence have characterized human use of nature throughout history: Humankind has increasingly expanded those parts of the ecosphere dominated, disrupted and destroyed by it. At the same time, levels of natural resource consumption have increasingly diverged within and among human societies. The counter-model - Contraction & Convergence - was initially developed for climate policy and future greenhouse gas emissions. The Wuppertal Institute has attempted to widen this into a general environmental policy model for the future in its Fair Future study, but did not conduct any precise quantification. Lovink, Wackernagel & Goldfinger have produced quantitatively more precise scenarios. They range from reducing natural resource consumption to 88% of global ecological capacity following the Brundtland Report, to a contraction to 50% as proposed by the biologist Wilson. Numerous difficulties stand in the way of realizing such concepts - for the price of their implementation would be severe reductions in the volume of output and stock of capital of economies and/or in the world population. Not least, both the prevailing socio-economic power structures and the fact, founded in evolutionary biology, that we are 'unfit for sustainability' and for deference to nature stand in the way of realizing C&C models.
Keywords: 330; expansion; divergence; contraction; convergence